Randomized trial of standard pain control with or without gabapentin for pain related to radiation-induced mucositis in head and neck cancer. Issue 6 (December 2016) - Kataoka, Tomoko; Kiyota, Naomi; Shimada, Takanobu; Funakoshi, Yohei; Chayahara, Naoko; Toyoda, Masanori; Fujiwara, Yutaka; Nibu, Ken-ichi; Komori, Takahide; Sasaki, Ryohei; Mukohara, Toru; Minami, Hironobu
Abstract: Objective: Radiation-induced mucositis (RIM) in chemoradiotherapy (CRT) for head and neck cancer (HNC) causes severe pain and worsens CRT compliance, QOL and outcome. Following retrospective reports, we conducted a randomized trial of the safety and efficacy of gabapentin for RIM-associated pain during CRT. Methods: HNC patients (pts) receiving CRT were randomized to standard pain control (SPC) with acetaminophen and opioids, or SPC plus gabapentin (SPC + G). Gabapentin was maintained at 900 mg/day for 4 weeks after CRT. Primary endpoint was maximum visual analogue scale (VAS) score during CRT, and secondary endpoints were total opioid dose, changes in QOL (EORTC QLQ-C30 and QLQ-HN 35) from baseline to 4 weeks after CRT, and adverse events. Results: Twenty-two eligible Stage III or IV pts were randomly assigned to SPC or SPC + G ( n  = 11 each). Twelve were treated in a locally advanced setting and 10 in a postoperative setting. Median maximum VAS scores, median total dose of opioids at maximum VAS and total dose of opioids at 4 weeks after CRT tended to be higher in the SPC + G arm (47 in SPC vs. 74 in SPC + G, p  = 0.517; 215 mg vs. 745.3 mg, p  = 0.880; and 1260 mg vs. 1537.5 mg, p  = 0.9438, respectively), without significance. QOL analysis showed significantly worse scores in the SPC + G arm for weight gain ( p  = 0.005). Adverse events related to gabapentin were manageable. Conclusions: This pilot study is the first prospective randomized trial of gabapentin for RIM-related pain. Gabapentin had no apparent beneficial effect. Further research into agents for RIM-related pain is warranted.